Game theory applications in the electricity market and renewable energy trading: A critical survey - Huang, Wen; Li, Heng (Frontiers in Energy Research, 2022)
With the acceleration of China's electricity market construction it is urgent to establish a unified electricity transaction mechanism, to balance the interests of all parties and build a competitive electricity market. Game theory has significant advantages in the study of decision optimization among multiple decision-making bodies that interact and compete with each other. Therefore, the application of game theory in the electricity system has attracted the attention and research of a large number of scholars, among which the research on the electricity market accounts for the highest proportion. In this paper, the concept and evolution of cooperative game theory, non-cooperative game theory and evolutionary game theory in game theory are described in detail. Secondly, the status quo and scale of the domestic and foreign electricity market are sorted out and summarized. Finally, according to the research results of the application of three kinds of game theory in the electricity market in recent years, the paper evaluates and analyzes the three typical aspects of the power generation side, the power sale side and the power consumption side, and puts forward the prospect of the application of game theory in the electricity market in the future.